Tourism Village Development Strategy In Lappa Upang Village, Mare District , Bone Regency , South Sulawesi - Rusli, Rusli; Hasniaty, Hasniaty (Pascasarjana STIE Amkop Makassar, 2024)
This research aims to analyze the management strategy for tourism village development in Lappa Upang Village, Mare District, Bone Regency, South Sulawesi . Indonesia is an archipelagic country that is rich in artistic, cultural and natural diversity. Thus encouraging enormous tourism potential with its uniqueness and characteristics. Along with the dynamics of tourism development, tourism activities are now not only concentrated in big cities. However, it has entered rural areas, as can be seen from the large number of villages that have succeeded in developing their village tourism potential , managed well so that they are able to increase Regional Original Income (PAD). Bone Regency is the largest district in South Sulawesi Province, its area even reaches 4,559 kilometers with a population of 801,775 people, spread across 27 sub-districts. The southern part of the coast, there is Mare District, is on the Poros City road, Bone Regency and Sinjai Regency. Lappa Upang Village, with a population of 1,618 people and an area of 16 km, was formed from three old villages, namely Cenrana, Ula and Sunebba villages which later became one village. Lappa Upang Village has ecotourism potential with natural attractions such as Mount Batu Lotong, Lappa Upang River, and Baruttung Waterfall. Cultural traditions such as the Mabbaruga ritual and typical local culinary delights enrich the attraction. This potential supports the development of the village as a national and international tourist destination. Based on the research results, it was found that Lappa Upang Village has great potential to develop as a tourist destination by utilizing internal strengths and external opportunities. Quadrant I position in the SWOT analysis shows that the village is in a very good situation to implement a development strategy that focuses on growth and development ( Growth and Build ). By implementing the right SO strategy, villages can achieve their long-term goals and improve the welfare of local communities.Keywords: Strategy, Development, Tourism Village,